In and Outs of Chuviridae Endogenous Viral Elements: Origin of a Potentially New Retrovirus and Signature of Ancient and Ongoing Arms Race in Mosquito Genomes - Dezordi, Filipe Zimmer; Vasconcelos, Crhisllane Rafaele dos Santos; Rezende, Antonio Mauro; Wallau, Gabriel Luz (Frontiers in Genetics, 2020)
Background: Endogenous viral elements (EVEs) are sequences of viral origin integrated into the host genome. EVEs have been characterized in various insect genomes, including mosquitoes. A large EVE content has been found in Aedes aegypti and Aedes albopictus genomes among which a recently described Chuviridae viral family is of particular interest, owing to the abundance of EVEs derived from it, the discrepancy among the chuvirus endogenized gene regions and the frequent association with retrotransposons from the BEL-Pao superfamily. In order to better understand the endogenization process of chuviruses and the association between chuvirus glycoproteins and BEL-Pao retrotransposons, we performed a comparative genomics and evolutionary analysis of chuvirus-derived EVEs found in 37 mosquito genomes. Results: We identified 428 EVEs belonging to the Chuviridae family confirming the wide discrepancy among the chuvirus genomic regions endogenized: 409 glycoproteins, 18 RNA-dependent RNA polymerases and one nucleoprotein region. Most of the glycoproteins (263 out of 409) are associated specifically with retroelements from the Pao family. Focusing only on well-assembled Pao retroelement copies, we estimated that 263 out of 379 Pao elements are associated with chuvirus-derived glycoproteins. Seventy-three potentially active Pao copies were found to contain glycoproteins into their LTR boundaries. Thirteen out of these were classified as complete and likely autonomous copies, with a full LTR structure and protein domains. We also found 116 Pao copies with no trace of glycoproteins and 37 solo glycoproteins. All potential autonomous Pao copies, contained highly similar LTRs, suggesting a recent/current activity of these elements in the mosquito genomes. Conclusion: Evolutionary analysis revealed that most of the glycoproteins found are likely derived from a single or few glycoprotein endogenization events associated with a recombination event with a Pao ancestral element. A potential functional Pao-chuvirus hybrid (named Anakin) emerged and the glycoprotein was further replicated through retrotransposition. However, a number of solo glycoproteins, not associated with Pao elements, can be found in some mosquito genomes suggesting that these glycoproteins were likely domesticated by the host genome and may participate in an antiviral defense mechanism against both chuvirus and Anakin retrovirus.